Tribe of hackers : cybersecurity advice from the best hackers in the world - Carey, Marcus J. (Cybersecurity professional); Jin, Jennifer (Wiley, 2019)
Tribe of Hackers: Cybersecurity Advice from the Best Hackers in the World is your guide to joining the ranks of hundreds of thousands of cybersecurity professionals around the world. Whether you're just joining the industry, climbing the corporate ladder, or considering consulting, Tribe of Hackers offers the practical know-how, industry perspectives, and technical insight you need to succeed in the rapidly growing information security market.- Resumé vydavatel
Keywords: kybernetická bezpečnost; počítačová bezpečnost; informační bezpečnost; cyber security; computer security; information security; elektronické knihy; sborníky; electronic books; papers of several authors